Avulsion fracture of the iliac crest in a football player - Valdes, M.; Molins, J.; Acebes, O. (Scandinavian Journal of Medicine & Science in Sports, 2000)
We describe an unsual injury of the iliac crest in an adolescent football player. The injury occured as a result of a sudden twist of the trunk while kicking. Plain radiographs showed avulsion fracture of the anterior part of the iliac crest apophysis. Five moths later the injury was partially ossificated but the patient felt minor pain and was not confident of returning to playing football.